2000
DOI: 10.1016/s1097-2765(00)00097-6
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Spo11 Gene Is Required for Meiotic Chromosome Synapsis

Abstract: The Spo11 protein initiates meiotic recombination by generating DNA double-strand breaks (DSBs) and is required for meiotic synapsis in S. cerevisiae. Surprisingly, Spo11 homologs are dispensable for synapsis in C. elegans and Drosophila yet required for meiotic recombination. Disruption of mouse Spo11 results in infertility. Spermatocytes arrest prior to pachytene with little or no synapsis and undergo apoptosis. We did not detect Rad51/Dmc1 foci in meiotic chromosome spreads, indicating DSBs are not formed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
686
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 741 publications
(732 citation statements)
references
References 49 publications
31
686
2
3
Order By: Relevance
“…Furthermore, activation of DNA damage repair is a normal event in meiosis. During meiosis induction of DSBs by Spo11‐endonuclease occurs in the leptotene spermatocytes as the chromosomes begin to pair, in the same cell type with a high E2f1 expression level (Baudat et al ., 2000; Romanienko & Camerini‐Otero, 2000). In zygotene spermatocytes the pairing is completed and DSB repair and meiotic crossing‐over commence in the pachytene phase.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of DNA damage repair is a normal event in meiosis. During meiosis induction of DSBs by Spo11‐endonuclease occurs in the leptotene spermatocytes as the chromosomes begin to pair, in the same cell type with a high E2f1 expression level (Baudat et al ., 2000; Romanienko & Camerini‐Otero, 2000). In zygotene spermatocytes the pairing is completed and DSB repair and meiotic crossing‐over commence in the pachytene phase.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its relation to meiotic cohesins, the AE formation occurs independently on recombination initiation (Romanienko and Camerini-Otero 2000) and vice versa (Yuan et al 2000) in the mouse although this takes place during leptotene as well. The induction of DSBs occurs prior/or simultaneously to the formation of the chromosome axes and is catalyzed by the evolutionarily highly conserved topoisomerase Spo11 in mouse as in the other organisms (Cole et al 2010).…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 96%
“…Only 5-10% of meiotic nuclei showed some degree of synapsis as indicated by the presence of SYCP1, SYCE1 and SYCE2 in this study. The synapsis, however, occurred mainly between non-homologous chromosomes (Baudat et al 2000;Romanienko and Camerini-Otero 2000;Bolcun-Filas et al 2009). Besides, different studies have reported about interactions between early proteins of the recombination machinery and SC components.…”
Section: Second Step: the Assembly Of The Central Regionmentioning
confidence: 99%
“…Here we show that mouse spermatogenesis genes are relatively underrepresented on the X chromosome and female-biased genes are enriched on it. We used Spo11 -/-mice blocked in spermatogenesis early in meiosis 12 to evaluate the temporal pattern of gene expression in sperm development. Genes expressed before the Spo11 block are enriched on the X chromosome, whereas those expressed later in spermatogenesis are depleted.…”
mentioning
confidence: 99%
“…The disruption of Spo11 in mice blocks meiosis before pachytene and interrupts normal testis development (Fig. 3a,b) 12,22 . In agreement with the marked changes in testis morphology in Spo11 -/-mice (Fig.…”
mentioning
confidence: 99%